ANALISIS WACANA LISAN DALAM INTERAKSI GURU DAN SISWA PADA MATA PELAJARAN BAHASA INDONEISA DI SMP AL-KARIMAH - Wahid Rhomadon Pratama; Sri Utami (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the structure of oral discourse used by teachers in the interaction of teachers and students in the classroom during the learning process. This research was conducted at SMP AL-KARIMAH with the object of research as many as 29 students. This study uses a descriptive qualitative method. The data obtained are oral discourse used by teachers and students during the learning process. The technique is using the listening and note-taking technique. The findings of this study are (1) initial/abstract. The teacher gives a prefix in the form of greeting. (2) Center/orientation. There are exchanges and transactions. the teacher gives an introduction to a question, the answer to an answer. And feedback based on answers in the form of questions. The start of the transaction by the teacher is marked by the teacher explaining something to the students, then directing students to focus on learning, and the teacher provoking students to provide feedback about what was discussed at that time. (3) End/Code. The teacher gives conclusion and closing.